New Advances and Contributions to Fish Biology - Türker, Hakan (IntechOpen, 2012)
This book provides an understanding on a large variety of related topics in fish biology. The further development on molecular and cellular biology and ecology leads to assimilate the newer scientific knowledge in this area. Leading research works from around the world are brought together in this book to produce a valuable source of reference for teachers, researcher, and advanced students of biological science. The fist three chapters of this book give a general description of the complex biology of the immune response. Detailed descriptions were also included on understanding of cytokine regulation in teleost immune system. The second three chapters provide information on the environmental stressors on the responses of freshwater fish across molecular to population level. Then, the following two chapters review two special topics; the roles of the atrium and the ventricle across teleost species and the tracer methodologies on the measurements of carbohydrate metabolism. The last chapter discusses the variables that are involved in the feeding behavior of a predatory freshwater fish species.